PCR-Restriction Enzyme Analysis for Detection of Candida DNA in Blood from Febrile Patients with Hematological Malignancies - Morace, Giulia (American Society for Microbiology, 1999)
Blood samples were drawn daily from 72 patients who had hematological malignancies, neutropenia, and fever and who had failed to respond to broad-spectrum antibiotics. Each sample was used for conventional fungal blood cultures and for detection and identification of Candida DNA by a PCR method with subsequent restriction enzyme analysis (REA) recently developed in our laboratory. The PCR method was able to detect five CFU of Candida spp. per ml of blood, and subsequent REA of the amplicons allowed the identification of the Candida species most commonly implicated in cases of candidiasis. Thirty-one patients were PCR-REA positive, and four of these patients were also culture positive. The ultimate diagnosis for 13 of these patients and 1 patient who was PCR-REA negative was disseminated candidiasis (confirmed by clinical data, multiple cultures, histology, autopsy, and/or ultrasonographic evidence of hepatosplenic candidiasis). The molecular method is significantly more sensitive than conventional fungal blood cultures and has a high negative predictive value (97.5%) for the development of disseminated candidiasis in neutropenic patients.